2022
DOI: 10.21203/rs.3.rs-2136713/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sociocultural factors associated with Detection of ASD among Culturally and Linguistically Diverse Communities in Australia

Abstract: Background This study aimed to characterise the most common types of first concerns observed by Australian parents regarding initial autism presentation, the average age of first concern (AOC), and associated sociocultural factors including culturally and linguistically diverse (CALD) background of the family. Methods A battery of measures relevant to demographics and information about ASD symptoms was completed for 760 participating children. Results The mean AOC was 18.2 months. The most common concerns w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Ou et al (14) found that even if the mother spoke English pro ciently, infants from culturally and linguistically diverse (CALD) communities were less likely to access health services and receive mental health interventions. A study by Hussain et al (15) found a signi cant link between CALD status and delayed age at which developmental concerns were raised, as well as higher severity of autism symptoms at the time of professional input. In this regard, a multicultural cohort study found an inverse care law in that those from the most disadvantaged backgrounds with the highest risk for developmental problems were least likely to engage with developmental Page 3/20 surveillance programs for early identi cation, thereby missing opportunities for early intervention (13,16).…”
Section: Introductionmentioning
confidence: 99%
“…Ou et al (14) found that even if the mother spoke English pro ciently, infants from culturally and linguistically diverse (CALD) communities were less likely to access health services and receive mental health interventions. A study by Hussain et al (15) found a signi cant link between CALD status and delayed age at which developmental concerns were raised, as well as higher severity of autism symptoms at the time of professional input. In this regard, a multicultural cohort study found an inverse care law in that those from the most disadvantaged backgrounds with the highest risk for developmental problems were least likely to engage with developmental Page 3/20 surveillance programs for early identi cation, thereby missing opportunities for early intervention (13,16).…”
Section: Introductionmentioning
confidence: 99%